Evangelia Stefani, Nikos Merousis and Anastasia Dimoula. A century of research in prehistoric Macedonia 1912-2012 - Maria Valamoti, Soultana (Journal of Greek Archaeology, 2016)
This volume is the fruitful outcome of an international conference dedicated to a century of prehistoric research in Macedonia. The conference was held within a wider framework of commemorations on the occasion of the centenary since the liberation of Thessaloniki from the Ottoman rule. The conference was organised by the Archaeological Museum of Thessaloniki, its director Polyxeni Adam-Veleni and a large team of the Museum’s archaeologists as well as Archaeology Professors from the Aristotle University of Thessaloniki. The volume, edited by Evangelia Stefani, Nikos Merousis and Anastasia Dimoula, presents a rich overview of prehistoric investigations conducted within the geographical area corresponding to the region of Macedonia in northern Greece. It comprises in total sixty papers written mostly in Greek (12 amongst them are written in English), with English abstracts, occasionally of substantial extent.